2021
DOI: 10.1021/acs.energyfuels.1c02231
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Ash Issues in Oxyfuel Combustion of Coal and Biomass: Mineral Matter Transformation, Ash Formation, and Deposition

Abstract: To alleviate the global warming issue, various CO 2 abatement technologies have been proposed. As one of the leading options for CO 2 capture in power plants mostly firing coal and biomass, the oxyfuel combustion technology has been actively developed for decades. Progress at different stages of the development has been continuously updated in several reviews. However, they usually cover a wide range of topics, which vary significantly in detail. The ash issues are very critical to the design and operation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…27,28 Moreover, the substitution of carbon dioxide instead of nitrogen in this technology helps to prevent the emission of NO x as an undesirable product of air combustion technology. 29 Yushiie et al 30 conducted experimental and numerical analysis on the effect of NO x formation in the oxyfuel combustion technology, and their results confirmed that NO x emissions under CO 2 −O 2 conditions were lower than those under "air" conditions. Oxyfuel combustion has been approved in several studies, by using different types of fuels, it can reduce NOx emissions.…”
Section: Monoethanolamine (Mea) Is a Useful Solvent In Industrialmentioning
confidence: 88%
“…27,28 Moreover, the substitution of carbon dioxide instead of nitrogen in this technology helps to prevent the emission of NO x as an undesirable product of air combustion technology. 29 Yushiie et al 30 conducted experimental and numerical analysis on the effect of NO x formation in the oxyfuel combustion technology, and their results confirmed that NO x emissions under CO 2 −O 2 conditions were lower than those under "air" conditions. Oxyfuel combustion has been approved in several studies, by using different types of fuels, it can reduce NOx emissions.…”
Section: Monoethanolamine (Mea) Is a Useful Solvent In Industrialmentioning
confidence: 88%
“…During pyrolysis, the majority of Cl is released into volatiles in the forms of HCl and/or chloromethane (CH 3 Cl) due to the interactions between Cl and biomass organic compounds, with ∼28% being retained in the biochar. This suggests another advantage of using biochar as a co-firing fuel because Cl-related operational problems (e.g., ash deposition and particulate matter emission) , can be largely mitigated.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…An extensive body of research has been dedicated to investigating ash deposition mechanisms, which are well-understood to include inertial impaction, eddy impaction, thermophoresis, condensation, and chemical reactions . Numerous review articles, each focusing on distinct research interests and published across different eras, have enriched our understanding of these processes. For instance, Kleinhans et al comprehensively analyzed the behaviors of ash particles sticking and rebounding, shedding light on their intricacies. Niu et al compiled key issues concerning ash deposition during biomass combustion, with a particular emphasis on the role of alkali species.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Cai et al critically reviewed the progression of ash deposition numerical simulation, encompassing aspects such as particle combustion and sticking, rebound, and removal behaviors. Yu et al offered a detailed review of ash deposition behavior in oxy-fuel combustion, concentrating on experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation